Service-oriented computing – ICSOC 2014 Workshops : WESOA ; SeMaPS, RMSOC, KASA, ISC, FOR-MOVES, CCSA and satellite events, Paris, France, November 3-6, 2014, Revised selected papers /: WESOA ; SeMaPS, RMSOC, KASA, ISC, FOR-MOVES, CCSA and satellite events, Paris, France, November 3-6, 2014, Revised selected papers. (2015) - Unknown
No abstract available